Efeitos regionais do Mercosul: uma análise diferencial-estrutural para o período 1990-1995 - Honório Kume; Guida Piani (Economia Aplicada, 1999)
The objective of this paper is to analyse the impacts of Brazilian trade with the other Mercosur countries on the regional production of industries in Brazil, from 1990 through 1995. First we estimated and analysed export and import coefficients for a group of states and for a large sample of industries.Then we applied the expanded shift-share analysis in order to obtain a quantitative evaluation ofthe impacts of trade with Mercosur countries on regional production.